PENGARUH KPOP BTS SEBAGAI BRAND AMBASSADOR DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKOPEDIA - Rizkie, Ricky (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
E-commerce is one of the keys to the development of the times where you can sell and buy needs online. As for the problem of target marketing competition to promote their respective e-commerce companies by choosing Brand Ambassadors as the main face of e-commerce itself which strengthens marketing so that visitors are interested and make the number of visitors increase. The purpose of this study is to find out and analyze the influence of brand ambassadors and brand images on consumer purchasing decisions at Tokopedia. The type of research used is explanatory research with research methods using questionnaire data collection. The data analysis model used is multiple linear regression analysis. The sample selection was carried out by means of purposive sampling. And the sample is 100 respondents, using multiple linear analysis. The results of the regression test show that 49.4% of purchasing decision factors can be explained by brand ambassadors and brand image, while the remaining 50.6% is explained by other factors that are not included in this study. While the results of the Ftest indicate that simultaneously the brand ambassador and brand image variables simultaneously have a positive and significant effect on purchasing decisions with the results of the analysis Fcount = (49.367) > Ftable = (3.090). The results of the ttest show that the Brand Ambassador variable shows the results of the tcount analysis (-1.821) and the Brand Image variable shows the results of the tcount analysis (9.089) where ttable (1.98472), so partially the Brand Ambassador variable has no significant effect on Purchasing Decisions, while the dominant variable is Brand Image on Purchasing Decisions. Keywords: Brand Ambassador, Brand Image, Purchase Decision